2022
DOI: 10.1093/jcbiol/ruab077
|View full text |Cite
|
Sign up to set email alerts
|

Observations on anchialine-pool shrimps (Decapoda: Caridea: Atyidae, Barbouriidae) from the Philippines: A re-assessment after four decades and discovery of a second epigeal pool

Abstract: We document the current status of the enigmatic bright-red anchialine shrimps in Tiniguiban Islet in the western Visayas region of the Philippines. A second epigeal anchialine pool was discovered in nearby Hinlaran Islet, and two shrimp species were recorded in the pools, the large barbouriid Parhippolyte uveaeBorradaile, 1900 as previously reported and a much smaller atyid Antecaridina lauensis (Edmondson, 1935). The shrimps move in and out of the pools with tidal fluctuations, since both pools completely dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The existence of phytoplankton was used to determine the availability of natural food in water and determine the water quality of an ecosystem [16][17][18]. An investigation reported that the intestinal contents of P. uveae consisted of foraminifera, algae, mucus, and chyme [19]. This shows that one of its natural foods is algae.…”
Section: Introductionmentioning
confidence: 99%
“…The existence of phytoplankton was used to determine the availability of natural food in water and determine the water quality of an ecosystem [16][17][18]. An investigation reported that the intestinal contents of P. uveae consisted of foraminifera, algae, mucus, and chyme [19]. This shows that one of its natural foods is algae.…”
Section: Introductionmentioning
confidence: 99%